Water Management in Rural Area with Nature-Based Solution: A Case Study of Valley Communities in Ban Pi, Ban Luang District, Nan Province, Thailand - Saithep, Nakrob; Nilanon, Onkamon; Vasuwattana, Attana (วารสารวิชาการภูมิสถาปัตยกรรมและการวางผัง, 2021)
This study focuses on the possibilities of water management in a rural valley community area by using the Nature-based solution as a concept. Study area is located in Ban Phi, Ban Luang District, Nan province, agricultural villages in Northern Thailand. In this study, the qualitative research method of collecting and analyzing data with the landscape ecology concept is applied. The result gains an understanding of human and landscape relationships, conditions, and potentials. Subsequently, reviews of nature-based solutions are required in order to develop the solutions in restoring ecosystem functions and human well-being. This area has a large amount of water supply in the wet season. Although reservoirs and check dams are constructed, the site unable to retain water in the dry season. The water management method demonstrates two solutions to deal with the site conditions and demands of water. The first solution, restoration of plant stripes on slopes and stream riparian areas to maintain soil moisture, filter, and reduce water runoff. Another solution is modifying agricultural water usage to be more efficient by integrated agroforestry system into traditional agriculture. With these solutions, green and blue infrastructures are created and enhanced to provide ecological functions on a landscape scale.